Sediment‐encased maturation: a novel method for simulating diagenesis in organic fossil preservation. (25th July 2018) - Saitta, Evan T.; Kaye, Thomas G.; Vinther, Jakob
Abstract: Exceptional fossils can preserve diagenetically‐altered biomolecules. Understanding the pathways that lead to such preservation is vital to utilizing fossil information in evolutionary and palaeoecological studies. Experimental taphonomy explores the stability of tissues during microbial/autolytic decay or their molecular stability through maturation under high pressure and temperature. Maturation experiments often take place inside sealed containers, preventing the loss of labile, mobile or volatile molecules. However, wrapping tissues inside aluminium foil, for example, can create too open a system, leading to loss of both labile and recalcitrant materials. We present a novel experimental procedure for maturing tissues under elevated pressure/temperature inside compacted sediment. In this procedure, porous sediment allows maturation breakdown products to escape into the sediment and maturation chamber, while recalcitrant, immobile components are contained, more closely mimicking the natural conditions of fossilization. To test the efficacy of this procedure in simulating fossil diagenesis, we investigate the differential survival of melanosomes relative to proteinaceous tissues through maturation of fresh lizard body parts and feathers. Macro‐ and ultrastructures are then compared to fossils. Similar to many carbonaceous exceptional fossils, the resulting organic components are thin, dark films composed mainly of exposed melanosomes resting on the sediment in association with darkened bones. Keratinous, muscle, collagenous and adipose tissues appear to be lost. Such results are consistent with predictions derived from non‐sediment‐encased maturation experiments and our understanding of biomolecular stability. These experiments also suggest that organic preservation is largely driven by the original molecular composition of the tissue and the diagenetic stability of those molecules, rather than the tissue's decay resistance alone; this should be experimentally explored in the future.